Micropaleontological record of Holocene estuarine stages in the Bahía Blanca estuary - Calvo Marcilese, María Lydia Valentina (2013)
Holocene paleoenvironmental changes have been interpreted on the basis of benthic foraminifera and calcareous nannofossils recovered in samples from Napostá Grande Stream, Bahía Blanca estuary, southern Buenos Aires Province. Samples are fine sands and clay sediments from a Holocene outcrop and were studied with quantitative techniques. The benthic foraminiferal assemblage is dominated by Ammonia parkinsoniana, A. tepida, Bolivina pseudoplicata, B. striatula, Bolivina sp., Buccella peruviana, and Elphidium spp. The calcareous nannofossil assemblage recovered is a typical cold-water association, dominated by Calcidiscus leptoporus, Coccolithus pelagicus, Emiliana huxleyi and Gephyrocapsa oceanica. A dendrogram classification by cluster analysis was made for each microfossil group. The results of these analyses were coincident, showing a liaison between changes in the assemblages of benthic foraminifera and calcareous nannofossils. Those results, jointly with the sedimentological information, lead to the identification of three different paleoenvironments along the Napostá N1 site. The lower part of the succession represents an estuarine environment with larger marine connection. The middle part represents a gradual passage to a more restricted estuarine environment, and the upper part represents the establishment of the modern continental fresh-water environment.